Electromagnetic wave scattering on a dielectric cylinder in Born approximation - Syshchenko, V.V. (Вопросы атомной науки и техники, 2015)
The scattering of the plane electromagnetic wave on a spatially extended, fiber-lake target is considered. The fomula for the scattering cross section is obtained using the approximation analogous to Born one in quantum mechanics.